Disease Control Priorities, Third Edition : Volume 8. Child and Adolescent Health and Development - Bundy, Donald A. P. (Washington, DC: World Bank, 2017)
About the Series From its inception, the Disease Control Priorities series has focused attention on delivering efficacious health interventions that can result in dramatic reductions in mortality and disability at relatively modest cost. The approach has been multidisciplinary, and the recommendations have been evidence-based, scalable, and adaptable in multiple settings. Better and more equitable health care is the shared responsibility of governments and international agencies, public and private sectors, and societies and individuals, and all of these partners have been involved in the development of the series. Disease Control Priorities, third edition (DCP3) builds upon the foundation and analyses of the first and second editions of Disease Control Priorities (DCP1 and DCP2) to further inform program design and resource allocation at global and country levels by providing an up-to-date comprehensive review of the effectiveness of priority health interventions. In addition, DCP3 presents systematic and comparable economic evaluations of selected interventions, packages, delivery platforms, and policies based on newly developed economic methods. DCP3 presents its findings in nine individual volumes addressed to specific audiences. The volumes are structured around packages of conceptually related interventions, including those for maternal and child health, cardiovascular disease, infectious disease, and surgery. The volumes of DCP3 will constitute an essential resource for countries as they consider how best to improve health care, as well as for the global health policy community, technical specialists, and students.